MECHANICAL CHARACTERIZATION OF A POLYESTER MATRIX COMPOSITE REINFORCED WITH NATURAL FIBERS FROM Luffa cylindrica Hoen (Nativa, 2023)
The growing demand for renewable products has led to many studies of alternative materials. The present work describes the production of a composite based in polyester resin reinforced with fibers from the climber plant Luffa cylindrica and evaluates its mechanical performance. The composite was produced with two perpendicularly-crossed layers of vegetable fibers. The lamination was performed in a mold with two glass plates pressed by a hydraulic press. To characterize the properties of the produced composite, density, tensile and bending strength tests were performed. The final composite had a mean density of 1.16 g cm-3, making it light due to the reinforcement with vegetable fibers. Tensile and bending strengths were 13.91 and 26.70 MPa, respectively. The experimental results showed that the composite with vegetable fibers as reinforcement had lower density than the pure polyester matrix and composites produced with glass fibers. The tensile strength was higher than the polyester matrix itself, although it was still low. Also, when submitted to bending stress, the composite presented lower resistance than the matrix. Overall, the composite can be a viable alternative for non-structural applications where light materials are required such as handicrafts and office partition.Keywords: sustainable material; vegetable fibers; mechanical properties; technical feasibility. Caracterização mecânica de um compósito com matriz de poliéster reforçado com fibras naturais de bucha vegetal (Luffa cylindrica Hoen) RESUMO: A crescente demanda por produtos renováveis tem levado a muitos estudos de materiais compósitos reforçado com fibras vegetais. A planta trepadeira Luffa cylindrica, conhecida popularmente como bucha vegetal, também apresenta potencial para este uso. O presente trabalho avalia o desempenho de um compósito à base de resina de Poliéster reforçado com bucha vegetal. O compósito foi produzido com duas camadas de fibras vegetais dispostas perpendicularmente entre si. A laminação foi realizada em um molde com duas placas de vidro prensadas por uma prensa hidráulica. Como propriedade física foi determinada a densidade e para as propriedades mecânicas, foram realizados ensaios de resistência à tração e flexão. O compósito final apresentou densidade média de 1,16 g cm-3, tornando-o leve devido ao reforço com fibras vegetais. As resistências à tração e flexão foram de 13,91 e 26,70 MPa, respectivamente. Os resultados experimentais mostraram que o compósito com fibras vegetais como reforço apresentou densidade menor que a matriz de poliéster pura e compósitos produzidos com fibras de vidro. A resistência à tração foi maior do que a própria matriz de poliéster. Além disso, quando submetido a tensões de flexão, o compósito apresentou menor resistência do que a matriz. No geral, o composto pode ser uma alternativa viável para aplicações não estruturais onde materiais leves são necessários, como artesanatos e paredes divisórias.Keywords: material sustentável; fibras vegetais; propriedades mecânicas; viabilidade técnica.